2002
DOI: 10.1002/jmri.10076
|View full text |Cite
|
Sign up to set email alerts
|

MRI‐guided thermal therapy of transplanted tumors in the canine prostate using a directional transurethral ultrasound applicator

Abstract: Purpose: To evaluate MRI-based techniques for visual guidance, thermal monitoring, and assessment during transurethral ultrasound thermal therapy of implanted tumors in an in vivo canine prostate model. Materials and Methods:Transmissible venereal tumors (TVT) were grown in the right lobe of the prostate in four dogs. High-temperature thermal therapy was selectively applied to the tumor-bearing lobe using a transurethral ultrasound applicator with a 180°directional heating pattern. Temperature-sensitive MRI (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
112
1

Year Published

2003
2003
2007
2007

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 93 publications
(117 citation statements)
references
References 33 publications
4
112
1
Order By: Relevance
“…To correct for tissue shrinkage due to processing, the distances between lesion centers before and after fixation were measured. An average shrinkage of 10% was observed and is similar to those reported in rabbit brain (22) and dog prostate (16).…”
Section: Measurement Of Lesion Area On Histopathologysupporting
confidence: 85%
See 3 more Smart Citations
“…To correct for tissue shrinkage due to processing, the distances between lesion centers before and after fixation were measured. An average shrinkage of 10% was observed and is similar to those reported in rabbit brain (22) and dog prostate (16).…”
Section: Measurement Of Lesion Area On Histopathologysupporting
confidence: 85%
“…Planning is usually based on MR-derived thermal indices, in which a coagulation threshold is adopted-in most studies either a dose of 240 minutes at 43°C or a minimum peak temperature of 55°C (8,12). While reports exist that the planned treatment volume agrees with histologically-confirmed necrotic tissue (16), there is greater evidence that this threshold is a conservative estimate (17). Studies by Chung et al (8) showed that the ablation volume was 25% larger than that planned in rabbit skeletal muscle, while a two-fold increase was shown in application to uterine fibroid treatment (B.J.…”
Section: High-intensity Focused Ultrasound (Fus)mentioning
confidence: 99%
See 2 more Smart Citations
“…(Current address: Department of Neurosurgery, Osaka University Medical School, 2-2 Yamadaoka, Suita, Oaska, 565-0871, Japan. Phone: +81-6-6879-3652: FAX: +81-6-6879-3659; e-mail : m-kinoshita@nsurg.med.osaka-u.ac.jp) hyperthermia, such as coagulation of tissues [1][2][3][4][5][6][7][8][9][10][11][12], mechnical tissue destruction [13,14], disruption of tight junctions of the vasculature for enhanced local drug delivery [15][16][17][18][19][20], and sonoporation, a transient enhanced permeability of the cell membrane caused by the combination of ultrasound and microbubbles [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. As all of these bio-effects can be created non-invasively in vivo, ultrasound is gathering a great attention as a next generation surgical or drug delivery system.…”
Section: Introductionmentioning
confidence: 99%